Trabajar con las Emociones en arteterapia - Duncan, Norman (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2007)
Emotions have a fundamental importance in human development and experience. In art therapy, working with the arts helps the personal and emotional development. The therapist can handle four phases to work with emotions in art therapy: naming, exploring, exercising and integrating.